Raconter sans inventer. Córdoba de los Omeyas d’Antonio Muñoz Molina - Geneviève Champeau (Cahiers de Civilisation Espagnole Contemporaine)
Córdoba de los Omeyas, by Antonio Muñoz Molina (1991), has been interpreted as belonging as well to literature as to historiography. Indeed, Muñoz Molina writes history in a literary way, by applying the techniques of travel and historical narrative to his own imaginary world. This hybrid narrative, whose subject is the Muslim Cordoba at his height, may be considered as a fable about our current political concerns, which are also at the center of the articles Muñoz Molina wrote in various newspapers.